2019
DOI: 10.1037/aca0000288
|View full text |Cite
|
Sign up to set email alerts
|

Can art change the way we see?

Abstract: Visual art is pervasive in modern society. From advertising to fine arts galleries, the visual arts play a visible role in how we view and understand the world. In this review, we consider research that speaks to whether our experiences with art can change the way we see. Numerous studies speak, often indirectly, to this question—addressing whether artists see things differently from nonartists. Specifically, we reviewed literature that investigates the ways artistic ability and artistic training interact with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 90 publications
1
3
0
Order By: Relevance
“…It is conceivable that even though art experience promotes expertise in art, it does not necessarily translate to enhanced holistic processing of faces in art. Our results are in line with a recent review of the literature (Benear et al, 2019) that found little support for the idea that experience in art could improve visual perception.…”
Section: Discussionsupporting
confidence: 86%
“…It is conceivable that even though art experience promotes expertise in art, it does not necessarily translate to enhanced holistic processing of faces in art. Our results are in line with a recent review of the literature (Benear et al, 2019) that found little support for the idea that experience in art could improve visual perception.…”
Section: Discussionsupporting
confidence: 86%
“…Investigating the dynamics of both visual attention and drawing strategies as an artwork emerges will provide additional insights on artists’ expertise. Crucially, eye movement strategies should be linked to behavioural advantages in local and global processing, so that they are grounded in an understanding of how they benefit perceptual decision making (Benear et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Crucially, eye movement strategies should be linked to behavioural advantages in local and global processing, so that they are grounded in an understanding of how they benefit perceptual decision making (Benear et al, 2019).…”
mentioning
confidence: 99%
“…A significant number of studies suggest that traditional drawing experts have acquired many skills such as better attention span, manipulation skills and better spatial skills (e.g., Orde 1997; Alias, Gray & Black 2002; McManus et al 2010; Perdreau & Cavanagh 2015; Contreras et al 2018; Benear et al 2019; Chamberlain et al 2021; Park, Wiliams & Chamberlain 2021). Drawing/sketching involves a wide range of major cognitive functions such as:…”
Section: Skills Needed For Traditional Sketchingmentioning
confidence: 99%